THEORETICAL AND EXPERIMENTAL INVESTIGATION OF IONIC-MEDIATED POLYMERIC MEMBRANES FOR ENHANCED CO2 SEPARATION. - Abubakkar Saddeeq (Nazarbayev University School of Sciences and Humanities, 2025)
The integration of graphene oxide and ionic liquids within polymeric membrane matrices is particularly advantageous for carbon dioxide (CO2) separation over other light gases, particularly CH4 and N2. This preferential affinity towards CO2 is due to the favorable quadrupolar interaction of CO2 between ionic liquids and graphene oxide, thereby promoting high selectivity and enhanced gas separation efficiency. Therefore, we report the series of four novel composite polymeric membranes through a photopolymerization of ionic CO2-philic crosslinkers, EG2 [VlmC6O2Vlm] [Tf2N]2 and EG3 [VlmC8O3Vlm] [Tf2N]2, which contain graphene oxide (GO) and free ionic liquids (1-butyl-3-methylimidazolium 2-(2 methoxyethoxy)-ethyl sulfate [BMIM][MDEGSO4]. The structural-property relationships of the four newly developed ILs-mediated GO-composite membranes were analyzed by thermogravimetric analysis (TGA), differential scanning calorimetry (DSC), and X-ray diffraction (XRD). The composite membranes were subsequently studied for their gas separation performance (CO2/CH4, CO2/N2) using a time-lag apparatus, while theoretically, the composite membranes were investigated for CO2 capture via the MD simulation method using the Gromacs package. The newly developed composite membranes presented excellent CO2 permeability and superior perm-selectivity (CO2/CH4 and CO2/N2), surpassing the 2008 Robeson’s upper bound limit of both CO2/CH4 and CO2/N2. Theoretically, the results obtained from MD simulations, such as radial distribution functions g(r), interaction energies, CO2 densities, and MSDs, also confirm the excellent capture ability of the composite materials towards CO2.
Keywords: Gas separation; CO2 capture; ILs-mediated GO-composite membranes; CO2 perm selectivity; MD simulations.; Type of access: Embargo